Evaluation of Staple Foods Supplemented with Defatted Coconut Testa Flour - Fareed, Rushdah; Ulpathakumbura, Savani; Yalegama, Chandi; Hewapathirana, Dilani; Marikkar, Nazrim (International Coconut Community Journal, 2022)
Coconut testa is an important byproduct of coconut processing. In this study, the acceptability of staple foods incorporated with defatted coconut testa flour (CTF) was investigated. Foods supplemented with CTF will be ideal as a functional food for diabetes. Formulations of string hoppers incorporated with CTF were done by mixing white rice flour (RF) with CTF in four different ratios; F1 (RF: CTF=70:30), F2 (RF: CTF=75:25), F3 (RF: CTF=80:20) and F4 (RF: CTF=85:15). Likewise, formulation of flat-bread rotti were prepared by mixing wheat flour (WF) with CTF in four different ratios; P1 (WF: CTF=60:40), P2 (WF: CTF=70:30), P3 (WF: CTF=80:20) and P4 (WF: CTF=90:10). Acceptability of the formulations was determined using Friedman test and preference ranking test. According to sensory evaluation, the highest score of overall acceptability and other sensory attributes were observed for composite flour mixtures incorporated with 25% of CTF in rice flour for string hoppers (idiyappa) and 20% of CTF in wheat flour for flat- bread (rotti). The proximate analysis of the finished products namely, string hopper (idiyappa) and flat-bread (rotti) showed better nutritional properties with regard to protein, dietary fiber, fat and mineral content than respective composite flour mixtures used in their preparation. Furthermore, IF and string hopper (idiyappa) samples showed increased nutritional compositions in terms of dietary fiber, mineral content when compared to RF and flat-bread rotti samples. In conclusion, the quality attributes and dietary fibre content of the two formulated products indicated their potential use as anti-diabetic foods.